2014
DOI: 10.1002/2013jd021227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of urban morphology configurations on the accuracy of urban canopy model temperature simulations with MODIS

Abstract: Simulations of the urban environment contribute to assessments of current and future urban vulnerabilities to extreme heat events. The accuracy of simulations of the urban canopy can be degraded by inaccurate or oversimplified representations of the urban-built environment within models. Using a 10 year (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) series of offline 1 km simulations over Greater Houston with the High-Resolution Land Data Assimilation System (HRLDAS), this study explores the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…Furthermore, we complement other studies that have applied land surface temperature (e.g. Li and Bou-Zeid, 2014;Monaghan et al, 2014;Ramamurthy et al, 2015) or vertical temperature profiles (e.g. Hu et al, 2010;Garcia-Diez et al, 2013;Trusilova et al, 2016) for evaluating PBL schemes and UCMs.…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, we complement other studies that have applied land surface temperature (e.g. Li and Bou-Zeid, 2014;Monaghan et al, 2014;Ramamurthy et al, 2015) or vertical temperature profiles (e.g. Hu et al, 2010;Garcia-Diez et al, 2013;Trusilova et al, 2016) for evaluating PBL schemes and UCMs.…”
Section: Introductionmentioning
confidence: 74%
“…NLDAS models used in this study (Noah, Mosaic, and VIC) compute ET as a fraction of potential ET derived with Penman‐Monteith equation [ Mahrt and Ek , ], using parameters that represent (1) soil moisture, (2) fractional vegetation cover, and (3) surface resistance [Noah —Chen et al ., ; Mosaic —Koster and Suarez , ; VIC— Liang et al ., ]. The associated errors are (1) underestimation of soil moisture caused by the absence of irrigation module, (2) misrepresentation of urban canopy because model grids (∼14 km) are larger than the scale of urban heterogeneity [ Monaghan et al ., ], and (3) inaccurate representation of urban canopy resistance that deviates from Penman‐Monteith scheme [ Litvak et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the simplicity of the irrigation scheme used by Monaghan et al . []—it simulated permanent uninterrupted irrigation of all greater Houston—it led to more realistic representation of latent heat flux compared to the original models. Unfortunately, direct comparison of our estimates with ET produced by such high resolution models was impractical because in their current state these models may not be applied to large heterogeneous areas such as Los Angeles municipal districts.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that both urban representations (bulk urban parameterization in Noah LSM and SLUCM) could adequately capture the main weather features over urban regions. However, in the following sections, detailed discussions are based on model results from WRF‐default and WRF‐modified, because of the large uncertainty in the specification of urban canopy parameters within SLUCM [ Liao et al , ; Monaghan et al , ; Adachi et al , ; Li et al , ].…”
Section: Methods and Datamentioning
confidence: 99%